2008
DOI: 10.1590/s1517-83822008000100032
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and potential use of monoterpenes as tropical fruits preservatives

Abstract: Banana, papaya and pineapple are the most consumed tropical fruits in the world, being Brazil one of the main producers. Fungi Colletotrichum musae, Colletotrichum gloeosporioides and Fusarium subglutinans f.sp. ananas cause severe post harvest diseases and losses in fruits quality. The aim of this work was to evaluate the effectiveness of five monoterpenes to inhibit the mycelial growth and conidia germination of these three phytopathogens. The monoterpenes citral, citronellal, L-carvone, isopullegol and α-pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 24 publications
0
51
0
4
Order By: Relevance
“…This phytoconstituent is active against HSV-1 in vitro and it has anti-inflammatory action, where it blocks the NF-κB pathway (Adorjan & Buchbauer, 2010). Garcia et al (2008) demonstrated the activity of citral against the fungi Colletotrichum musae, Colletotrichum gloeosporioides and Fusarium subglutinans f.sp. ananas.…”
Section: Research Articlementioning
confidence: 99%
“…This phytoconstituent is active against HSV-1 in vitro and it has anti-inflammatory action, where it blocks the NF-κB pathway (Adorjan & Buchbauer, 2010). Garcia et al (2008) demonstrated the activity of citral against the fungi Colletotrichum musae, Colletotrichum gloeosporioides and Fusarium subglutinans f.sp. ananas.…”
Section: Research Articlementioning
confidence: 99%
“…Outra consequência negativa do uso de agrotóxicos é a seleção de raças do patógeno resistentes a doses crescentes (Ghini & Kimati, 2000). Para minimizar este impacto, o uso de fungicida nas doses recomendadas, a rotação do principio ativo e do modo de ação, bem como, a busca de produtos alternativos no controle de fitopatógenos, entre eles, o uso de compostos do metabolismo secundário de plantas, tem sido constantemente pesquisado.…”
Section: Introductionunclassified
“…Most of the aroma from citrus fruit oil, cherries, and mint is due to the high content of monoterpenes, but they have no nutritional value because they are exclusively vegetable (Serrano et al,2006). Studies have shown that monoterpenes have various pharmacological properties including antifungal, antibacterial, antioxidant, anticancer, and anti-spasmodic (Garcia et al, 2008;Kato et al, 1990;Singh et al, 2010;Karkabounas et al, 2006;Magalhães et al, 1998).…”
Section: Introductionmentioning
confidence: 99%